Low Serum Albumin Is Associated with Poor Prognosis in Patients Receiving Peritoneal Dialysis Treatment. (18th April 2022) - Shi, Yanan; Cai, Jiajie; Shi, Chunxia; Liu, Conghui; Zhou, Jingjing; Li, Zhongxin
Abstract : Background . The number of patients receiving dialysis treatment is sustainably increasing, especially peritoneal dialysis. Objectives . It is necessary to find out potential factors that may indicate the prognosis of patients receiving peritoneal dialysis treatment. Methods . This study retrospectively involved 325 patients who received peritoneal dialysis treatment. Results. Low serum albumin (HR = 2.254; 95% CI: 1.534–3.311; P < 0.001 ) and high FBG (Fasting blood glucose) (HR = 1.474; 95% CI: 1.025–2.120; P = 0.037 ) were risk factors for death in patients receiving peritoneal dialysis treatment. Serum albumin (AUC = 0.683; P < 0.001 ) and creatinine (AUC = 0.625; P < 0.001 ) exhibited value of prognosis prediction. Both high FBG (P = 0.005 ) and low albumin (P < 0.001 ) were associated with poor prognosis, and low albumin predicted poorer survival. Conclusions . Low serum albumin and high fasting blood glucose were risk factors and associated with poor prognosis. Low albumin has a potential in predicting the prognosis of patients receiving peritoneal dialysis treatment.